2013
DOI: 10.1097/iae.0b013e3182695b83
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab Plus Grid Laser Photocoagulation or Intravitreal Bevacizumab or Grid Laser Photocoagulation for Diffuse Diabetic Macular Edema

Abstract: The study provides evidence to support the use of primary IVB with or without GLP as treatment of diffuse diabetic macular edema. Primary IVB without GLP seems to be superior to GLP alone to provide stability or improvement in best-corrected visual acuity in patients with diffuse diabetic macular edema at 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 31 publications
(28 reference statements)
1
31
1
2
Order By: Relevance
“…In the Protocol T, to achieve a totally dry macula, laser needed to be done after six months of intravitreal therapy in 41%, 52%, or 64% of the patients treated with aflibercept, ranibizumab, or bevacizumab, respectively. However, in a meta-analysis of 12–36 months of follow-up studies, no differences were found in this regard between ranibizumab monotherapy and combined with laser [32], and in a multicentric study comparing bevacizumab monotherapy versus combination with laser, bevacizumab showed better functional and anatomic results at 24 months than combination therapy [33]. …”
Section: Discussionmentioning
confidence: 99%
“…In the Protocol T, to achieve a totally dry macula, laser needed to be done after six months of intravitreal therapy in 41%, 52%, or 64% of the patients treated with aflibercept, ranibizumab, or bevacizumab, respectively. However, in a meta-analysis of 12–36 months of follow-up studies, no differences were found in this regard between ranibizumab monotherapy and combined with laser [32], and in a multicentric study comparing bevacizumab monotherapy versus combination with laser, bevacizumab showed better functional and anatomic results at 24 months than combination therapy [33]. …”
Section: Discussionmentioning
confidence: 99%
“…The 2-year follow-up demonstrated the beneficial effect of IVB with or without grid laser photocoagulation for diffuse DME. [5960]…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Three commonly used intravitreous VEGF inhibitors — aflibercept (Eylea, Regeneron Pharmaceuticals), bevacizumab (Avastin, Genentech), and ranibizumab (Lucentis, Genentech) — have been shown to be beneficial and relatively safe for the treatment of diabetic macular edema, 6,1518 but only aflibercept and ranibizumab are approved by the Food and Drug Administration (FDA) for this indication. Bevacizumab, which is not approved by the FDA for any ocular indication, is widely used for off-label treatment of diabetic macular edema in repackaged aliquots containing approximately 1/500th of the systemic dose used in cancer therapy.…”
mentioning
confidence: 99%